Application of semi-endless rolling technology in CSP production line. (November 2020) - Zhou, Feng; Chen, Xuewen; Gao, Jixiang; Li, Liejun; Zhou, Qing
Abstract: The technical problems and relating reasons of semi-endless rolling were introduced in this paper. Regarding the problems, we carried out a series of improvement towards these problems. The application of semi-endless rolling got a great success.